1998
DOI: 10.1046/j.1365-2249.1998.00618.x
|View full text |Cite
|
Sign up to set email alerts
|

Pirfenidone induces intercellular adhesion molecule-1 (ICAM-1) down-regulation on cultured human synovial fibroblasts

Abstract: SUMMARYPirfenidone has been shown to modify some cytokine regulatory actions and inhibit fibroblast biochemical reactions resulting in inhibition of proliferation and collagen matrix synthesis by fibroblast. We have investigated the effect of pirfenidone on the expression of cell adhesion molecules. The synovial fibroblasts were treated with IL-1a in the presence or absence of pirfenidone (range 0-1000 mM), and assayed for the expression of adhesion molecules such as ICAM-1 and endothelial-leucocyte adhesion m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 23 publications
0
52
1
1
Order By: Relevance
“…7,10,30,[42][43][44] The present results suggest that PFD attenuates CHF-related arrhythmogenic atrial remodeling via a complex set of actions, affecting multiple levels and components of the fibrosis formation and degradation signaling cascade.…”
Section: Effects Of Pirfenidonementioning
confidence: 70%
“…7,10,30,[42][43][44] The present results suggest that PFD attenuates CHF-related arrhythmogenic atrial remodeling via a complex set of actions, affecting multiple levels and components of the fibrosis formation and degradation signaling cascade.…”
Section: Effects Of Pirfenidonementioning
confidence: 70%
“…Hale and coworkers reported that pirfenidone reduced staphylococcal enterotoxin B-induced cytokine levels and T-cell proliferation in a murine shock model and in vitro human peripheral blood lymphocyte assays (18). Moreover, pirfenidone induced intracellular adhesion molecule-1 downregulation on cultured human synovial fibroblasts (47). These results suggest that pirfenidone may be promising as a new therapeutic strategy for patients with asthma who have airway structural changes and remodeling in response to persistent inflammation.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, it has been shown to lessen pulmonary fibrosis by modulating the fibroproliferative actions of transforming growth factor-β in cultured human fibroblasts [79]. Encouraging results have recently been reported from a double-blind, placebo-controlled study evaluating the treatment effect of pirfenidone in 107 patients with idiopathic pulmonary fibrosis.…”
Section: Treatmentmentioning
confidence: 99%